Analysis of the Implementation of PTOS-M (Pelindo Terminal Operation - Multipurpose) at PT Pelabuhan Tanjung Priok Branch Cirebon - Ayutia, Yolla; J.Najoan, Denny; Fatimah, Aida Nur (Institut Ilmu Sosial dan Manajemen Stiami, 2024)
This study aims to determine the effect of implementing PTOS-M (Pelindo Terminal Operation System-Multipurpose) at PT Pelabuhan Tanjung Priok Branch Cirebon using the SWOT analysis method (Strength, Weakness, Opportunity, Threat). SWOT analysis was carried out using the IFAS (Internal Factor Analysis Strategy) matrix, which describes the strengths and weaknesses of PTOS-M, and the EFAS (External Factor Analysis System) matrix, which describes the opportunities and threats factors. From the results of the data analysis, obtained a total score of strengths, weaknesses, opportunities, and threats, and each obtained the highest strength weight of 3.8, the highest weakness weight of 1.6, the highest opportunity weight of 3.4, and the highest threat weight of 1.6. The average total score on the IFAS matrix is 2.2, while the EFAS matrix is 1.8. The result of this study is that PTOS-M is very influential on the company and it is highly recommended if this system is good to be implemented in all branches.